Entrepreneurial Leadership and Innovation Capabilities for Startup Growth in Emerging Digital Markets - Murphy Mutie; Dwi Andayani; Yane Devi Anna; Gautam Khanna (Pandawan Sejahtera Indonesia, 2025)
Digital startups in Indonesia are facing increasingly fierce competition and rapid technological change. These conditions require companies to have a high level of adaptability to survive and thrive. The background of this research is based on the importance of entrepreneurial leadership and innovation capability as two factors believed to support business sustainability and growth in the digital era. The purpose of this research is to analyze the extent to which these two factors contribute to the growth of digital startups in Indonesia, particularly in the context of emerging markets that face different challenges than developed countries. The research was conducted using a quantitative survey based method. The instrument used was a questionnaire with a Likert scale of 1–5, distributed to founders and managers of digital startups in Indonesia. The collected data were then analyzed using multiple linear regression to examine the relationship between entrepreneurial leadership, innovation capability, and digital startup growth. The results show that entrepreneurial leadership has a positive and significant influence in providing visionary strategic direction, improving decision-making capabilities, and fostering business resilience in the face of market uncertainty. Meanwhile, innovation capability has been shown to play a crucial role in strengthening competitive advantage through the creation of digital products and services relevant to consumer needs. The conclusion of this study confirms that the synergy between entrepreneurial leadership and innovation capability is a key factor in driving the growth of digital startups in Indonesia. However, this study is still limited by a relatively small number of respondents. Therefore, future research is recommended to expand the sample size and consider additional variables, such as the role of the digital ecosystem, access to funding, and sustainability strategies, to provide a more comprehensive picture.